CAPITAL INTENSITY, TRANSFER PRICING, DAN POLITICAL CONNECTIONS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SUB SEKTOR INDUSTRIAL GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Heni Yusnita (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This research aims to test and analyze the partial and simultaneous effects of Capital intensity, Transfer pricing, and Political connections on Tax avoidance in Industrial goods Sub Sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. This research was conducted on companies in the Industrial goods Sub-Sector listed on the Indonesia Stock Exchange during the period of 2019-2023. The type of data used in this study is secondary data. The research method used is a quantitative method. The sampling technique in this study employs purposive sampling method. The number of companies that meet the criteria to be sampled in this research is 9 companies. The data analysis method used is multiple linear regression analysis using SPSS version 27 software. The research results indicate that partially, Capital intensity, Transfer pricing, and Political connections have an effect on Tax avoidance in companies in the Industrial goods sub-sector listed on the Indonesia Stock Exchange during the period of 2019-2023. Simultaneously, Capital intensity, Transfer pricing, and Political connections affect Tax avoidance in companies in the Industrial goods sub-sector listed on the Indonesia Stock Exchange during the period of 2019-2023